SINGING DATA OVER THE PHONE: A SOCIAL HISTORY OF THE MODEM - Driscoll, Kevin (AoIR Selected Papers of Internet Research, 2015)
The modem is a singularly powerful symbol of late-20th century personal computer networking. Operating at the junction of computing and communication, the modem was a device that both defined and defied boundaries during the early history of the net. Amid the rapid deregulation of U.S. telecommunications during the 1970s, modems enabled thousands of far-flung microcomputer enthusiasts to exchange data and ideas over standard telephone wires. As PC ownership grew more commonplace during the 1980s, the modem became a mark of distinction, differentiating the everyday home computer owner from the small but growing telecomputing vanguard. Despite the technical and cultural significance of the personal computer modem, the device received scant attention in the scholarly literature of the 1980s and 1990s. Early theoretical work in internet studies seldom mentioned the modem except to illustrate the basic apparatus required for participation.1 And yet, among all other devices, it was the modem that drew internet communication out of the office and the research lab and into the intimate domestic space of the home. With the benefit of historical distance, this paper takes up the modem as its central object of study, listening in on the social, technical, and political resonances that can be heard amid the hiss and buzz of the modem’s song. The present historiography draws on an unusual collection of literature and electronics culled from the informal archives of retro-computing homepages, swap meets and eBay auctions. As the modem migrated from telecommunications arcana to consumer product, it was discussed in a variety of technical journals, hobbyist magazines, how-to books and electronic FAQs. Likewise, the industrial organization, design, and marketing of modems changed with the mass diffusion of networked personal computing during the 1980s and 1990s. Surviving devices from this period, along with the floppy disks, cassettes, manuals, and other ephemera with which they were originally sold, provide an additional set of primary sources for this project. A modem is an instrument of mediation placed in-between two otherwise dissimilar systems. This paper is similarly organized around three interrelationships transformed by the modem: sound and data, experimentation and standardization, and time and space.